Direct electrochemical generation of organic carbonates by dehydrogenative coupling - Gieshoff, Tile; Trieu, Vinh; Heijl, Jan; Waldvogel, Siegfried R. (Beilstein Journal of Organic Chemistry, 2018)
Organic carbonates are an important source for polycarbonate synthesis. However, their synthesis generally requires phosgene, sophisticated catalysts, harsh reaction conditions, or other highly reactive chemicals. We present the first direct electrochemical generation of mesityl methyl carbonate by C–H activation. Although this reaction pathway is still challenging concerning scope and efficiency, it outlines a new strategy for carbonate generation.
Keywords: anode; boron-doped diamond; dehydrogenative coupling; electrochemistry; organic carbonates